Peningkatan profesionalisme guru melalui pelatihan model belajar bahasa inggris daily language - Kaltsum, Honest Ummi; Hidayat, Muhamad Taufik; Astuti, Wili (Penamas: Journal of Community Service, 2022)
Because English is a global language, mastery of it is a necessity, especially for academics such as teachers and lecturers. English as a foreign language is not used as a daily language like English as a second language; it is only used and taught in schools during class hours. The purpose of this community service is to train teachers to improve their daily English language skills with the daily language application. The method of implementing the activities is divided into preparation, implementation, and monitoring of community service. This service is carried out online using Zoom meetings with 20 teachers. English as a foreign language is not used as a daily language like English as a second language; it is only used and taught in schools during class hours. Daily language is a mobile learning tool, so it is flexible for teachers and can be adapted to their hobbies in practice.